RELIGIOUS MODERATION IN JAVANESE CULTURE IN THE COMMUNITY OF TRIRENGGO VILLAGE, BANTUL, YOGYAKARTA - Joko Tri Haryanto (Penamas, 2022)
The phenomenon of radicalism and violence with religious nuances encourages the emergence of a discourse of religious moderation. Religious moderation is expected to direct a moderate, tolerant, and friendly related to the balance between religious commitment and the attitude toward religious relations. Indonesian people, especially the Javanese people, along with their rich culture and traditions, can encourage the discourse of religious moderation based on local culture in the form of social practices, institutions, and various traditions. This article reveals the practice of religious moderation in Javanese culture, which is grounded in the behaviour and way of life of the people of Trirenggo Village, Bantul Regency, Yogyakarta. The research was conducted using qualitative methods through data collection techniques in the form of observation, interviews, and focus group discussions (FGD). The study results show that the Javanese cultural values ​​adopted by the Trirenggo community teach an attitude of living in harmony with the environment, including relationships among residents and religious adherents. Various social activities show Javanese cultural values ​​that are in harmony with religious moderation carried out interfaith and the Javanese's social view of life, manners, and work concepts. The traditional expression as a reflection of the philosophy of life is internalized into self-awareness and morality, and externalization is in the form of views and moderation behaviour in carrying out social relations in society. The Trirenggo people construct themselves as Javanese people who get along harmoniously through moderate attitudes and behaviour. Thus, Javanese culture can be important for strengthening religious moderation in society.